Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
The answer is below
Explanation:
Prove that:
[tex]\frac{1+sinQ}{1-sinQ}=(secQ + tanQ)^2[/tex]
Trigonometric identities are equalities involving trigonometric functions for which both sides of the equality are equal and defined. Some trigonometric identities are:
sin²Ф + cos²Ф = 1; 1/cosФ = secФ; 1/sinФ = cosecФ; cosФ/sinФ = cotФ; 1 + tan²Ф = sec²Ф
Given:
[tex]\frac{1+sinQ}{1-sinQ}\\\\Divide\ through\ by \ cosQ:\\\\ \frac{\frac{1}{cosQ} +\frac{sinQ}{cosQ} }{\frac{1}{cosQ} -\frac{sinQ}{cosQ} }=\frac{secQ+tanQ}{secQ-tanQ}\\\\Next, rationalize\ the\ denominator\ by \ multiplying\ the\ numerator \ and\ \\denominator\ by\ secQ+tanQ:\\\\\frac{secQ+tanQ}{secQ-tanQ}*\frac{secQ+tanQ}{secQ+tanQ}=\frac{(secQ+tanQ)^2}{sec^2Q+secQtanQ-secQtanQ-tan^2Q}\\\\=\frac{(secQ+tanQ)^2}{sec^2Q-tan^2Q} ;\ But sec^2Q-tan^2Q=1,hence:\\\\[/tex]
[tex]\frac{(secQ+tanQ)^2}{sec^2Q-tan^2Q} =\frac{(secQ+tanQ)^2}{1}=(secQ+tanQ)^2\\\\\frac{1+sinQ}{1-sinQ}=(secQ+tanQ)^2[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.